Improvement of potato based cropping patterns by inclusion of short duration Mungbean and T. Aman rice in Monga prone areas of Rangpur - Islam, MK; Mahfuz, MS; Ghosh, S; Ali, ASMY; Hasnat, MZ (International Journal of Agricultural Research, Innovation and Technology, 2015)
The experiment was carried out to compare the improved cropping patterns against the farmers existing potato based cropping patterns having no mungbean/brown manure crop for higher yield, economic return and income generation in agricultural field in the off period following RCBD design with three replications at farmers field at Paikan Gangachara, Rangpur district during September- October. The treatments (cropping patterns) were T1 = T. aman rice (BINA 7) - Potato - Mungbean (BARI mungbean 6) (Improved pattern), T2 = T. aman rice (BR11) - Potato - Fallow (Farmers pattern), T3 = T. aman rice (BINA 7) - Potato + Maize intercrop - Mungbean (Improved pattern) and T4 = T. aman rice (BR11) - Potato / Maize relay (Farmers pattern). The highest yield (4.16 t ha-1) was recorded in T2 (BR11) which is statistically at par with T4 (4.15 t ha-1) but higher than the other treatments. Early planting sole potato (T1) gave highest yield (26.10 t ha-1) which was significantly higher than all other treatments. Late planting sole potato (T2), intercropped early potato (T3) and relay potato (T4) showed similar yield (23.61 24.79 t ha-1). Intercropped (T3) and Relay (T4) maize did not vary significantly in the studied parameters and yields were 8.21 and 7.92 t ha-1, respectively. Mungbean after sole potato (T1) gave higher number of pods/plant (17.25), and yield (1.47 t ha-1) which is significantly higher than those of T3 (14.89 and 1.28 t ha-1, respectively). Highest gross return (GR) (Tk. 417720) and gross margin (GM) (Tk. 220220) were calculated in improved pattern T3 and the lowest of those (Tk. 289670, Tk. 146020) in farmers pattern T2 . The other improved pattern T3 was the second highest performer considering GR and GM. But BCR (2.21) was highest in T1 and second highest in T3. The results indicated that the improved patterns (T1, T3) were better than farmers pattern (T2, T4). The improved pattern (T1) gave GR Tk. 67890 and GM Tk. 51785 higher than farmers pattern (T2). Similarly, the other improved pattern (T3) showed Tk. 51870 and Tk. 37395 higher than farmers pattern (T4). The improved pattern T1 and T3 created 45 working day job for the labour for harvesting early matured rice in the Monga/ jobless period (October) while farmers pattern gives only 3 days work. The mungbean included improved cropping patterns can be suggested for increased production, economic return and Monga mitigation (work opportunity in off period) in Rangpur. DOI: http://dx.doi.org/10.3329/ijarit.v4i2.22645 Int. J. Agril. Res. Innov. & Tech. 4 (2): 35-40, December, 2014